2006
DOI: 10.1007/s10750-005-1276-0
|View full text |Cite
|
Sign up to set email alerts
|

Germination Requirement of Vallisneria natans Seeds: Implications for Restoration in Chinese Lakes

Abstract: Due to eutrophication submerged macrophytes have disappeared from many Chinese lakes. This is unfortunate as submerged macrophytes are important to improve water quality, and its re-establishment is therefore desirable. For this purpose a potential method to use is re-seeding, this being particularly attractive due to the high seed productivity of V. natans. We conducted laboratory studies to investigate the effects of five environmental variables (temperature, substratum, oxygen, light availability, and buria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…For example, some field observations have confirmed that freshwater macrophytes can grow (albeit minimally) below thick layers of ice during wintertime (Boylen and Sheldon, 1976). Nonetheless, if we exclude a limited number of laboratory experiments and in situ observations that have investigated the response of submerged plants to temperature and underwater light regime (Ke and Li, 2006;Jarvis and Moore, 2008), hardly any data concerning the relationship between macrophyte depth distribution and temperature exist. Schwarz et al (2000) have identified the temperature as a secondary factor in modulating the performance of macrophytes, while Middleboe and Markager (1997), and Duarte and Kalff (1987) have considered the latitude as a cofactor in defining Zc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some field observations have confirmed that freshwater macrophytes can grow (albeit minimally) below thick layers of ice during wintertime (Boylen and Sheldon, 1976). Nonetheless, if we exclude a limited number of laboratory experiments and in situ observations that have investigated the response of submerged plants to temperature and underwater light regime (Ke and Li, 2006;Jarvis and Moore, 2008), hardly any data concerning the relationship between macrophyte depth distribution and temperature exist. Schwarz et al (2000) have identified the temperature as a secondary factor in modulating the performance of macrophytes, while Middleboe and Markager (1997), and Duarte and Kalff (1987) have considered the latitude as a cofactor in defining Zc.…”
Section: Discussionmentioning
confidence: 99%
“…Water temperature exerts a strong influence on macrophyte life phases, such as reproduction, germination and seedling emergence (Barko et al, 1982;Madsen and Adams, 1988;Spencer and Ksander, 1992;Leck, 1996;Xiao et al, 2010). Overall, the onset of germination in freshwater submerged macrophytes has been associated with temperatures ranging between ~23 and 29°C (Ke and Li, 2006;Jarvis and Moore, 2008). Moreover, lake thermal conditions can indirectly influence the macrophytes distribution by influencing the vertical stratification of phytoplankton.…”
Section: Discussionmentioning
confidence: 99%
“…In other Vallisneria species, such as V. natans and V. australis, seed viability is high over a range of environmental conditions and represents a means of survival when vegetative survival is low due to prolonged desiccation or salinity (Choudhuri, 1996;Ke and Li, 2006;Salter et al, 2008Salter et al, , 2010. For V. spinulosa investment in sexual reproduction may therefore be vital under circumstances of unpredictable environmental conditions for long-distance dispersal, while the species relies more heavily on local dispersal of asexual clones through tuber survival (Santamaria, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Substrates consisted of a mixture of two parts campus soil (a yellow-brown earth silt type) and one part standard potting compost from the Anhui Academy of Agricultural Sciences, mixed to evenness and used in all stages of all the experiments. Earlier studies have shown that V. spinulosa germinates and grows robustly in a range of substrates from gravels to silt (Ke and Li, 2006). Water from the university supply (not chlorinated and left to stand for 2−3 days before use) was used in all experiments, which resulted in average nitrogen and phosphorus levels of 0.95 (±0.145 95% CI) mg·L −1 and 0.18 (±0.039 95% CI) mg·L −1 within the microcosms.…”
Section: > Experimental Protocolsmentioning
confidence: 99%
“…The dense structure of the debris would prevent Spartina from emerging from deeper than 1 cm due to the exhaustion of food reserves before getting to the surface (Martínez et al 1992;Bond et al 1999). It has been previously described how deeply sown seedlings in sediment died before emerging in wetlands (Hartleb et al 1993;Jurik et al 1994;Wang et al 1994;Dittamar and Nelly 1999;Spencer and Ksander 2002;Ke and Li 2006). Live and dead standing biomass of Spartina patens (Aiton) Muhl prevented seedling emergence of subordinate annuals and perennials in coastal marshes (Brewer and Grace 1990;Baldwin et al 1996).…”
Section: Wrack Depth (Cm)mentioning
confidence: 99%